Intramolecular palladium-catalyzed alkene carboalkynylation. Issue 35 (2nd September 2015) - Nicolai, Stefano; Swallow, Peter; Waser, Jerome
Abstract: Carbocycles are essential building blocks for the synthesis of natural and synthetic bioactive compounds. Herein, we report the first example of palladium-catalyzed intramolecular carboalkynylation of non-activated olefins. Using activated carbonyl compounds as nucleophiles and an alkynyl bromide as an electrophile, the reaction gives access to cyclopentanes in 44–93% yield and one example of cyclohexane in 31% yield with simultaneous formation of a SP 3 –SP C–C bond. The reaction therefore combines ring formation with the introduction of a versatile triple bond for further functionalization. Graphical abstract: